Intuitionistic Fuzzy Soft Hypergraph - Thilagavathi, S.; ., . (International Journal of Engineering and Technology, 2018)
In this paper the notions of intuitionistic  fuzzy soft hypergraph and strong intuitionistic  fuzzy soft hypergraph are introduced. Also studied about union of two intuitionistic  fuzzy soft hypergraphs with suitable examples..